The Manners Concept According to Ki Hajar Dewantara and Hamka - Alfi Mar'atul Khasanah (Educan : Jurnal Pendidikan Islam, 2019)
Today's young generation, spends much of its time just playing Play station, Gedget, online games, and so on. That is what makes them empty of local cultural values, as well as foreign to terms such as manners, manners, mutual cooperation and other noble values in daily life. The world of education also feels the impact of modernity. All inventions of advanced technology today have unexpected effects. The development of civilization that is increasingly advanced has a significant influence, it can be seen from the attitude displayed in everyday life has been far from the personality of the nation. The impact of globalization that is happening at this time makes Indonesian people forget about national character education. In fact, character education is a very important foundation of the nation and needs to be instilled early on in children. By re-instilling character education in educational activities in schools, it will provide a solid grip on life for students to make students able to clarify and determine attitudes in choosing new cultures that enter. This article aims to explain the concept of character according to two Indonesian education leaders, namely Ki Hajar Dewantara and Hamka. They have different backgrounds for each other's thoughts. This is an interesting thing to observe.